Eco-floristic sectors and deforestation threats in Sumatra: identifying new conservation area network priorities for ecosystem-based land use planning - Laumonier, Y.; Uryu, Y; Stuwe, M.; Budiman, A.; Setiabudi, B.; Hadian, O. (2010)
Biogeographical studies are a necessary step in establishing conservation area networks. Determining the ecological factors influencing vegetation is also a basic principle for hierarchical ecological classifications and a necessary prerequisite for ecosystembased land use planning. Eco-floristic sectors (EFS) have already been identified for the Indonesian island of Sumatra, combining both approaches, dividing it into 38 EFSs representing unique ecosystems in terms of tree flora and environment (Laumonier 1997). The impact of deforestation on individual EFSs has been highly varied and in some cases extreme. We assigned one of five ‘extinction risk categories’ to each EFS based on the percentage of forest lost between 1985 and 2007. Eighty-five percent of all forest loss (10.2 million ha) occurred in the eastern peneplain, western lowland regions and swamps. In 2007, only 29% of forests were protected by conservation areas, only nine of the 38 EFS had more than 50% of their remaining forest cover protected. 38% of remaining forest was ‘‘critically endangered’’, ‘‘endangered’’ or ‘‘vulnerable’’ EFSs (5 million ha) but only 1 million ha (20%) were protected. Sumatra’s existing network of conservation areas does not adequately represent the island’s ecosystems. Priorities for a new conservation area network can be formulated for integration into Sumatra’s new land use plans at provincial